The global war for Internet governance - DeNardis, Laura 1966- author. (New Haven : Yale University Press, 2014)
The Internet governance oxymoron -- Controlling Internet resources -- Setting standards for the Internet -- Cybersecurity governance -- Governance at the Internet's core -- Internet access and network neutrality -- The public policy role of private information intermediaries -- Internet architecture and intellectual property -- The dark arts of Internet governance -- Internet governance and Internet freedom.